Implementation of Lecture Method to Improve Student Learning Achievement in Islamic Education Learning at SMA Negeri 1 Aceh Barat Daya - Nazarwati; Lisda (ETNOPEDAGOGI: Jurnal Pendidikan dan Kebudayaan, 2024)
This study aims to determine whether the application of the lecture method can improve the learning outcomes of class X students in Islamic Religious Education subjects in the aspect of Achieving Success Through Competing in Goodness and Work Ethic. The subjects in this study were class X E-1 students at SMA Negeri 1 Aceh Barat Daya. This study is a Classroom Action Research consisting of 2 cycles, namely cycle I, cycle II. Each cycle is a series of activities each consisting of 4 stages, namely planning, implementation, observation and reflection. This Classroom Action Research uses data collection methods, namely oral tests, observation sheets and documentation. Data analysis used by comparing the achievement of learning outcomes in each cycle is marked by an increase in the minimum completeness criteria or using descriptive-qualitative. The results obtained from this study are an increase in the learning outcomes of class X-E1 students in Islamic Religious Education subjects in the aspect of the Qur'an Achieving Success Through Competing in Goodness and Work Ethic. The average class in the pre-cycle stage was 6.78, in cycle I it increased to 75.89, in cycle II it increased again to 83.75. And classical completeness in the pre-cycle stage was 22.2%, in cycle I it became 75.4%, in cycle II it increased again to 83.75%. Based on these learning outcomes, it can be concluded that through the lecture method, it can improve the learning outcomes of class X E-1 students in the subject of Islamic Religious Education in the aspect of the Al-Qur'an, the Material Achieving Success Through Competing in Goodness and Work Ethic for the 2022-2023 Academic Year.